Evaluación bacteriológica y fúngica del aire y superficies en las diferentes áreas de los centros veterinarios - Bravo Solórzano, Anthony Josué (2023)
Nosocomial infections have become a problem of sanitary importance in hospital centers. The objective of this study was to evaluate the quality of air and surfaces in the different areas of the veterinary centers in Calceta parish from the bacteriological and fungal perspective in order to promote the importance of sanitary quality. For the collection of surface samples, the swab technique was used, while for air samples, the plate sedimentation technique was used, the plates were incubated and then the colony count was performed. For the identification of bacteria, Gram staining was used and for fungi, the simple staining technique was used. The results obtained determined the presence of bacteria and fungi in all the air samples, also bacteria were found on the surfaces of the door knob, armchair, desk, scale, examination table, phonendoscope, mayo table and surgical lamp and no presence was found on the surgical table, On the other hand, no fungi were found in the examination table and the surgical lamp, in most samples a high concentration of bacteria and fungi were found, highlighting the Gram + bacteria and fungi of the genus Fusarium and Mucor in the air and surface samples. The results described suggest high contamination of the air and surfaces of the veterinary centers evaluated.